"SCIENCE–RELIGION SAMVADA" AND THE INDIAN CULTURAL HERITAGE: with Nidhal Guessoum, "Islam and Science: The Next Phase of the Debates"; and Anindita Niyogi Balslev, "'Science–Religion Samvada' and the Indian Cultural Heritage". Issue 4 (December 2015) - Balslev, Anindita Niyogi
Abstract: This article seeks to delineate some of the fundamental philosophical traits that are special characteristics of the Indian cultural soil. Tracing these from the Vedic period, it is shown that this heritage is still alive and gives a distinctive flavor to the science–religion dialogue in the Indian context. The prevalent attitude is not to view science and religion as antagonistic, but rather as forces that together could create a world where the persistent epistemological and ethical problems can get resolved to the benefit of humanity. In Indian thought rationality and spirituality are not viewed as opposed categories. The notion of "evidence" has played a crucial role in all enquiries for legitimizing the sources of knowledge and the criteria by which any claim to knowledge can be tested. References to investigations pertaining to such areas as cosmology, ecology, ethics, study of consciousness, and so on are made in order to bring out their relevance for science–religion dialogue today.